2022
DOI: 10.1021/acs.jpcb.2c01252
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Layer Thickness in Frontal Polymerization

Abstract: Thermal frontal polymerization (FP) is a chemical process during which a cold monomer−initiator mixture is converted into a hot polymer as a polymerization front propagates in the system due to the interplay between heat diffusion and the exothermicity of the reaction. The theoretical description of FP generally focuses on one-dimensional (1D) reaction−diffusion (RD) models where the effect of heat losses is encoded into an effective parameter in the heat equation. We show here the limits of such 1D models to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 34 publications
3
10
0
Order By: Relevance
“…For thicker layers, the reaction outcompetes thermal cooling. Similar to the layer thickness study by Tiani et al, 105 instabilities in thin-film geometries with thermally insulating substrates were recently reported by Gao et al 124 The existence of convective and thermal instabilities has significant repercussions for FP chemistries and FP-derived materials. 112 In certain structural applications that require homogeneous features, for example, these non-uniform propagation motifs induce hot-spots that may negatively affect the properties of the final polymer.…”
Section: Instabilities In Frontal Polymerizationsupporting
confidence: 72%
See 2 more Smart Citations
“…For thicker layers, the reaction outcompetes thermal cooling. Similar to the layer thickness study by Tiani et al, 105 instabilities in thin-film geometries with thermally insulating substrates were recently reported by Gao et al 124 The existence of convective and thermal instabilities has significant repercussions for FP chemistries and FP-derived materials. 112 In certain structural applications that require homogeneous features, for example, these non-uniform propagation motifs induce hot-spots that may negatively affect the properties of the final polymer.…”
Section: Instabilities In Frontal Polymerizationsupporting
confidence: 72%
“…where h is the heat transfer coefficient (W m -2 K -1 ), and P (m) and S (m 2 ) are the perimeter and surface area of the domain cross-section, respectively. [103][104][105] Combining eqs 7-9, a final 1-D expression of heat conservation describes the evolution of temperature with time inside a control volume: As discussed in Section 2.3.3, ideal FP systems only exhibit large temperature changes in close proximity to the reaction zone (i.e., small Lθ and Lα on the scale of 0.1 to 1 mm). The final governing equation (11) illustrates several key physical properties that modulate effective front propagation.…”
Section: 𝜕𝛼mentioning
confidence: 99%
See 1 more Smart Citation
“…However, at the interface, the higher of unstable fronts have a nonmonotonic dependence on d r due to the thermal spikes. The effect of the layer thickness on front velocity and temperature is similar when FP is subjected to convective heat loss …”
Section: Resultsmentioning
confidence: 96%
“…Therefore, leveraging the competition between the heat generated by the reaction and the thermal transport enables the tuning of key features that influence the efficiency and feasibility of FP, that is, the front shape, velocity, and temperature. , Moreover, thermochemical instabilities emerge at a critical reaction–thermal transport power balance, potentially resulting in polymeric parts with complex geometries and heterogeneous properties . A recent numerical study has reported that the resin layer thickness controls the front dynamics and determines its existence subject to convective heat loss . Nevertheless, a quantitative relationship between front propagation, resin amount, and substrate effects is still lacking.…”
Section: Introductionmentioning
confidence: 99%